Effect of rare earth nucleating agent on supercritical CO2 foaming behavior of block copolymerized polypropylene. Issue 2 (March 2022) - Zhang, Yun; He, Yadong; Xin, Chunling; Su, Yanbin
The rare earth nucleating agent was used to modify block copolymerized polypropylene (PPB) in foaming process. The results show that the crystallization of PPB and the melting temperature of β-crystal increased gradually with increased β-crystal nucleating agent content. The total crystallinity decreased with amount of addition increasing, and the relative content of β-crystal increased first and then decreased. When β-crystal nucleating agent content was 0.4 wt%, the relative β-crystal content reached the maximum value of 95.27%, and the final crystal grain refinement significantly. The addition of rare earth β-crystal nucleating agent has a good effect on improving the uniformity of foam cells. Under the same content of β-crystal nucleating agent and pressure, the average cell diameter and expansion ratio increased with the saturation temperature increasing. After the foaming temperature reaches 155°C, the expansion ratio began to decrease, which was also consistent with the changed trend of relative β-crystal content. At the same content of temperature and relative β-crystal, as the foaming pressure increased, the cell diameter decreased gradually, and the expansion ratio increased first, and then decreased.